PENINGKATAN KEPERCAYAAN ORANG TUA MELALUI STRATEGI PEMASARAN SYARIAH DI PUSAT JAGAAN MALAYSIA - Adjie Akbar Damanik, Muhammad; Rahmayati, Rahmayati (Berajah Journal, 2024)
The aim of the research is to determine sharia marketing strategies in increasing public trust in the Bestari Impian care center, Malaysia. Strategy to build public trust by demonstrating the center's commitment to Sharia principles and providing an educational environment that is in line with Islamic values. The research method used in this research is a qualitative research method. The data collection techniques used are observation, interviews, documentation and data validity techniques. The results of this research show that the marketing strategy used is to provide guarantees of good service quality, partnerships with the community, marketing via social media, self-development programs, excellent customer service, feedback and evaluation and collaboration with sharia financial institutions.